PARTISIPASI MASYARAKAT DAN PENGINTEGRASIAN KEARIFAN LOKAL DALAM PENGELOLAAN PENDIDIKAN SEBAGAI BENTUK PELAKSANAAN DESENTRALISASI PENDIDIKAN - Karlina Kader; Abdurrahman Kader (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2019)
Education decentralization is the demand for education delivery change of government affairs that cannot avoid. This decentralization provides an opportunity for the actively involvedcommunity in education management. This study discusses community participation in education management and local wisdom integration in decentralization implementation of education. Communityinv olvementcan strengthen the national education system. Besides, increasing the curriculum structure by incorporating positive live local wisdom values and develop in each regional community can provide more outputs value of national education. The values have integrated with people's lives will be easily practiced by students in their daily lives. With this habit, it will become the culture in social life finally answer the nation's moral problems.